2022
DOI: 10.1177/15563316221114135
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Synthetic Polytetrafluoroethylene (PTFE) vs Human Dermal Allograft (HDA), 2 vs 3 Glenoid Anchors, and Suture vs Minitape in Superior Capsule Reconstruction

Abstract: Background: Superior capsule reconstruction (SCR) is an option for the treatment of massive, irreparable rotator cuff tears. However, which materials yield the strongest constructs remains undetermined. Purposes: We sought to investigate whether SCR with polytetrafluoroethylene (PTFE) or human dermal allograft (HDA), 2 or 3 glenoid anchors, and suture or minitape resulted in better failure load properties at the patch-glenoid interface. Methods: We conducted a biomechanical study in 30 glenoid-sided SCR repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that patients treated with interposition rotator cuff repairs experienced significant improvements in clinical outcome scores that were maintained a decade postoperatively 2,3 . The use of synthetic polytetrafluoroethylene (PTFE) has been validated in the treatment of irreparable rotator cuff tears, and has been shown to possess superior load‐to‐failure properties when compared with conventional human dermal allograft 4 . However, the best technique of securing grafts, irrespective of material, to the torn tendon edge has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that patients treated with interposition rotator cuff repairs experienced significant improvements in clinical outcome scores that were maintained a decade postoperatively 2,3 . The use of synthetic polytetrafluoroethylene (PTFE) has been validated in the treatment of irreparable rotator cuff tears, and has been shown to possess superior load‐to‐failure properties when compared with conventional human dermal allograft 4 . However, the best technique of securing grafts, irrespective of material, to the torn tendon edge has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The use of synthetic polytetrafluoroethylene (PTFE) has been validated in the treatment of irreparable rotator cuff tears, and has been shown to possess superior load-to-failure properties when compared with conventional human dermal allograft. 4 However, the best technique of securing grafts, irrespective of material, to the torn tendon edge has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Fascia lata was the original graft material used. However, biomechanical studies have found human dermal allograft and synthetic polytetrafluoroethylene (PTFE) provide comparable structural properties [ 17 , 18 , 19 ]. Furthermore, patch grafts circumvent the need to harvest autografts and the associated donor site morbidity [ 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%